Case Study 2 - Andhra Pradesh, India : Participation in Macroeconomic Policy Making and Reform - World Bank (Washington, DC, 2012)
For the past six years, the State of Andhra Pradesh in India has been at the vanguard of efforts to modernize the economy and the state while pursuing policies to improve the lives of the poorest. The Chief Minister and head of the ruling Telugu Desam Party (TDP), Mr. Chandra Babu Naidu, is known by some as the "Laptop Minister" for his modernizing initiatives. He has reached out to international organizations and investors but has also maintained his base of support at home, in part through expanded programs in education, health, and rural development. "I have initiated so many things," Naidu said. "They are going on and will pay off after some time. But people need something today." The challenges facing the government are daunting. Andhra Pradesh (AP) is one of the largest and poorest states in India. Its population of almost 80 million approaches that of the Philippines, the 13th most populous country in the world. Even as its high-tech industries develop rapidly, AP's overall literacy rate remains a modest 44% and one-third of the population lives in poverty.